NCR negative group 3 innate lymphoid cell (NCR−ILC3) participates in abnormal pathology of lung in cigarette smoking‐induced COPD mice - Shuyuan Chu; Libing Ma; Xia Yang; Bo Xiao; Yaxi Liang; Shaojie Zheng; Linqiao Li (Immunity, Inflammation and Disease, 2023)
Abstract Background Natural cytotoxicity receptor negative innate lymphoid cell (NCR−ILC3) involves into mucosal homeostasis, inflammation regulation and tissue remodeling. The proportion of NCR−ILC3 is increased in the lung of smokers with chronic obstructive pulmonary disease (COPD). However, there's still few understandings on the role of NCR−ILC3 in COPD pathogenesis. Methods COPD mice were induced by cigarette smoking. The pathology in lung was detected in histology. The frequency of NCR−ILC3 (CD3‐CD45+RORγt+NkP46‐) from murine lung was detected using flow cytometry. IL‐17+RORγt+ double positive cells in lung were assessed by double immunofluorescence staining. The protein expressions of epithelial‐to‐mesenchymal transition (EMT) markers, namely E‐cadherin and Vimentin, were assessed using immunohistochemistry staining and western blotting. Results The frequency of NCR−ILC3 in lung was higher in COPD group than controls. The IL‐17+RORγt+ cells in lung from COPD mice were more than controls. E‐cadherin expression was decreased but Vimentin expression was increased in lung of COPD mice, when compared with controls. The frequency of NCR−ILC3 in lung tissues were positively correlated with mean linear intercept in lung, destructive index in lung and EMT, respectively. Conclusions NCR−ILC3 could contribute to emphysema and EMT in lung of cigarette smoking‐induced COPD, which will provide further understanding on COPD pathogenesis of immune response.